2014
DOI: 10.1007/s10620-014-3267-3
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Vitamin D Levels Are Associated with Severe Histological Features and Poor Response to Therapy in Patients with Autoimmune Hepatitis

Abstract: Low 25(OH)D levels are associated with advance fibrosis and severe inflammation in AIH. Our study suggests that vitamin D may be a potential biomarker that predicts response to therapy and histological features in AIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 19 publications
3
69
1
Order By: Relevance
“…Polymorphisms in the VDR have been shown to increase susceptibility to certain autoimmune disorders, such as CD, type 1 diabetes, and inflammatory bowel diseases [34,35]. Furthermore, Vit D deficiency has been linked to a number of autoimmune disorders, including Crohn's disease, multiple sclerosis, AIH, PBC, psoriatic arthritis, and type 1 DM [36,37,38,39,40,41,42]. However, there are other studies that challenge these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in the VDR have been shown to increase susceptibility to certain autoimmune disorders, such as CD, type 1 diabetes, and inflammatory bowel diseases [34,35]. Furthermore, Vit D deficiency has been linked to a number of autoimmune disorders, including Crohn's disease, multiple sclerosis, AIH, PBC, psoriatic arthritis, and type 1 DM [36,37,38,39,40,41,42]. However, there are other studies that challenge these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Low serum levels of 25-hydroxyvitamin D have been reported in diverse chronic liver diseases [314][315][316][317][318], including autoimmune hepatitis [319,320], and this deficiency has been associated with disease severity and hepatic fibrosis. Hepatic fibrosis scores and interface hepatitis are independently associated with vitamin D deficiency in autoimmune hepatitis, and the serum level of 25-hydroxyvitamin D may be a biomarker of the histological response to severe or protracted tissue damage [319]. It may also reflect the integrity of an interactive network of counter-regulatory mechanisms that modulate oxidative stress, inflammatory activity, and immune defense.…”
Section: Insights Into the Cytopathic Mechanisms Of Autoimmune Hepatitismentioning
confidence: 99%
“…After adjustment for the sampling timing, vitamin D deficiency was an independent factor associated with advanced liver fibrosis. Some studies have shown a correlation between vitamin D level and liver fibrosis 14,17,33. These studies were based on liver biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Grünhage et al 16. evaluated liver disease of various etiologies, and Efe et al 17. evaluated autoimmune liver disease, with regard to the inverse relationship between serum vitamin D level and liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%